2020
DOI: 10.1007/s00401-020-02228-5
|View full text |Cite
|
Sign up to set email alerts
|

Mosaic trisomy of chromosome 1q in human brain tissue associates with unilateral polymicrogyria, very early-onset focal epilepsy, and severe developmental delay

Abstract: Polymicrogyria (PMG) is a developmental cortical malformation characterized by an excess of small and frustrane gyration and abnormal cortical lamination. PMG frequently associates with seizures. The molecular pathomechanisms underlying PMG development are not yet understood. About 40 genes have been associated with PMG, and small copy number variations have also been described in selected patients. We recently provided evidence that epilepsy-associated structural brain lesions can be classified based on genom… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 31 publications
(31 citation statements)
references
References 66 publications
(68 reference statements)
0
29
0
Order By: Relevance
“…Since then, evidence was provided for a targetable key gene regulatory role of DNA methylation in the process of epileptogenesis and chronification of seizures (58) as well as for the etiology‐dependence of such molecular findings in different animal models of epilepsy (59). This finding was validated in structural brain lesions associated with human focal epilepsy, mainly MCDs including major FCD subtypes and PMG (35, 60). These data support the development of a DNA methylation‐based disease classification system also for focal epilepsy, and the high level of standardization of such an approach has great promise to reduce the substantial inter‐observer variability observed in current MCD histopathological diagnostics (61).…”
Section: Dna Methylation‐based Disease Classification In Epilepsymentioning
confidence: 65%
See 1 more Smart Citation
“…Since then, evidence was provided for a targetable key gene regulatory role of DNA methylation in the process of epileptogenesis and chronification of seizures (58) as well as for the etiology‐dependence of such molecular findings in different animal models of epilepsy (59). This finding was validated in structural brain lesions associated with human focal epilepsy, mainly MCDs including major FCD subtypes and PMG (35, 60). These data support the development of a DNA methylation‐based disease classification system also for focal epilepsy, and the high level of standardization of such an approach has great promise to reduce the substantial inter‐observer variability observed in current MCD histopathological diagnostics (61).…”
Section: Dna Methylation‐based Disease Classification In Epilepsymentioning
confidence: 65%
“…In a series of 26 PMG patients, Kobow et al identified a group of seven patients exhibiting a unique molecular fingerprint, including the invariable detection of a brain mosaic duplication of the entire long arm of chromosome 1 and a specific genomic DNA methylation signature. This molecular profile was associated with a combination of characteristic clinical features, including a unilateral rather than focal and isolated PMG lesion, early‐onset epilepsy in the first months of life, and severe combinatorial developmental delay, thereby defining a new distinct PMG entity (35). In general, copy number variants are thought to contribute up to 5% of epilepsy cases.…”
Section: Brain Somatic 1q Trisomymentioning
confidence: 99%
“…Characteristic genomic methylation signatures for different disease stages have been reported in various species, etiologies, and pathologies [ 15 , 16 , 17 , 18 , 57 , 58 ]. A comprehensive integration and comparison of genomic DNA methylation data obtained in the present study (WGBS), with published data from different rat epilepsy models (Methyl-Seq), and human focal epilepsy (Methyl-Seq, Illumina arrays) has not yet been performed.…”
Section: Discussionmentioning
confidence: 99%
“…Epigenetic alterations were more recently also proposed as a fundamental pathomechanism in epilepsy. Several studies have identified locus-specific and genome-wide alterations in DNA methylation patterns in experimental epilepsy models [ 15 , 16 ] or human surgical brain samples [ 17 , 18 ]. Aberrant DNA methylation was linked to the compromised execution of gene expression programs and thereby suggested to account for many known structural and functional changes in the epileptic brain [ 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…The increasing revelation of genetic drivers associated with specific lesion patterns is very helpful to advance this field, as it offers new pharmaco‐therapeutic targets. The development of DNA methylation profiling in human brain diseases, in particular brain tumors has been another illuminating methodology to help clarify the clinico‐pathological and molecularly defined disease entities (9, 10).…”
Section: Introductionmentioning
confidence: 99%